Life of John Brown - Harner, James William (My University, 1900)
Introduction: John Brown’s ancestors on his father’s side came over from England in the Mayflower. They were characterized by having large families, and living to be very old; some of them reaching one hundred years. On his mother’s side, the family came from England at an early date. Both families produced warriors who fought in the War of 1812. Some of them were at one time members of the legislature of the state in which they lived, and also held other offices of responsibility. They were always respected, law abiding citizens. Captain John Brown, the son of Owen and Ruth brown, was born in Farmington, Litchfield County, Connecticut, May 9, 1800. When he was five years old, his father moved to Ohio. His father learned the art of tanning, then he began raising sheep and cattle for a living. John was sent to a friend of his father’s to be taught, but when he was nearly ready to enter college, his eyes were so weakened by hard study that he was compelled to give up all school work. He had early been taught at home to fear God and to treat man and beast with the utmost kindness. He frequently went on long journeys with droves of cattle, driving them alone. It was during one of these journeys that he saw a slave misused, and he then and there declared eternal war against slavery. When he was fifteen years old he went into the tanning business under his father. It is said that he would not sell the leather until it was entirely dry for fear of selling water as leather.
Citation: Harner, James William. Life of John Brown. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: John Brown; Biography; History; Theses